Systematic Literature Review: Nilai-nilai Pendidikan dalam Kewirausahaan Islam: Systematic Literature Review: Educational Values in Islamic Entrepreneurship - Lestari, Sinta; Nurpriatna, Ade; Hasanah, E.; Ismatullah, Ade; Malik, Muhammad Ibnu (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2024)
This study addresses the rising unemployment rate among vocational graduates in Sukabumi, Indonesia, by exploring the integration of Islamic values into entrepreneurship education. The core issue lies in the mismatch between graduates’ skills and labor market needs, compounded by insufficient emphasis on ethical entrepreneurship in Islamic institutions. Through a systematic literature review, this research analyzes how Islamic principles honesty (sidq), trustworthiness (amanah), justice (‘adl), and excellence (ihsan) can create sustainable, ethical businesses. Data were extracted from Scopus, Google Scholar, and peer-reviewed journals (2014–2024) using keywords like